Societal Vulnerability to Impacts of Extreme Weather Events on Land Transport Infrastructure Societal Vulnerability to Impacts - Luskova, Maria; Titko, Michal; O’Connor, Alan (Communications - Scientific letters of the University of Zilina, 2018)
The paper is focused on understanding how failure of land transport infrastructure leads to societal vulnerability. It presents the multilevel approach to societal vulnerability measuring. The level of the societal vulnerability is expressed through the Vulnerability Index, which is calculated based on the vulnerability indicators. Identification and selection of those indicators are based on definition of vulnerability as a function of exposure, susceptibility to change and capacity to adapt to that change.